Electron structure of apatite-like compounds with isomorphic substitution in tetrahedral positions - Shpak, A.P.; Karbovskii, V.L.; Kurgan, N.A.; Getman, E.I.; Senkevich, A.I.; Marchenko, V.I. (Functional Materials, 2005)
Effect of isomorphic anionic substitutions in the apatite-like calcium structures on their electron structure has been investigated. Changes in the electron subsystem of the first synthesized compounds Са₁₀(РО₄)₆-ₓ(VО₄)ₓ(М₂) (where М = F⁻,СI⁻, х - 0, 1, 3, 5, 6) caused by isomorphic anionic substitutions have been investigated using spectral and structural methods. It is established that fluorine and chlorine containing compounds are characterized by a general behavior tendency of the local electronic densities on calcium and oxygen atoms at the variation of anionic group number that evidences the electron structure independence of the anion type on the c-axis. Дослiджено вплив анiонних iзоморфних замiщень у апатитоподiбних структурах кальцiю на їх електронну будову. Спектральними та структурними методами дослiджено змiни у електроннiй пiдсистемi вперше синтезованих сполук Са₁₀(РО₄)₆-ₓ(VО₄)ₓ(М₂) (де М = F⁻,СI⁻, х - 0, 1, 3, 5, 6) при iзоморфних анiонних замiщеннях. Встановлено, що сполуки з фтором та хлором характеризуються загальною тенденцiєЮ поведiнки локальної електронної густини на атомах кальцiю та кисню при варiюваннi кiлькостi анiонних груп, що свiдчить про незалежнiсть електронної структури вiд типу анiона на осi c. Исследовано влияние анионных изоморфных замещений в апатитоподобных структурах кальция на их электронное строение. Спектральными и структурными методами исследованы изменения в электронной подсистеме при изоморфных анионных замещениях впервые синтезированных соединений Са₁₀(РО₄)₆-ₓ(VО₄)ₓ(М₂) , где М = F⁻,СI⁻, х - 0, 1, 3, 5, 6). Установлено, что соединения с фтором и хлором характеризуются общей тенденцией поведения локальной электронной плотности на атомах кальция и кислорода при варьировании количества анионных групп, что свидетельствует о независимости электронной структуры от типа аниона на оси c.